Assessment of Mandibular Condylar Morphology Using Digital Orthopantomogram in Chennai Population - Sridhar M1 , Sreedevi Dharman2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objective: The present study was performed to evaluate the variation in shapes of mandibular condyle, determine the predominant shape and to assess any peculiarities in either gender in an Orthopantamogram(OPG). Materials and Method: Radiographic evaluation of 3200 condylar heads after analyzing 1600 digitalized OPG’s were done. On analyzing, there were four different morphology of condyles observed. Variations occurring in the shapes were assessed, and combinations of the condylar shapes present in the population were established. Result: Of 1600 pairs of condylar heads evaluated, 78% were oval in shape, followed by diamond (12%), crooked finger (6%) and least being bird beak (3%). Oval-oval was commonly occurring combination (60.5%) whereas crooked finger-bird beak combination was found to be very rare. Conclusion: Dental professionals must have thorough knowledge in differentiating between normal and abnormal condyle morphology in an OPG as it possess a diagnostic challenge for them. Asymmetries that occur in condyle morphologies radiographically in absence of clinical signs and symptoms of TMDs are considered to be normal.